Peran Komunikasi Guru Pendidikan Agama Islam Dalam Pembinaan Akhlak Siswa SMP Negeri 36 Makassar - Ahmad Riyadhi Sultan; Nur Setiawati; Andi Hasriani (Jurnal Ilmiah Islamic Resources, 2021)
This research aims to know the communication role of Islamic Religious Education Teachers in fostering the morals of seventh grade students of SMP Negeri 36 Makassar and to know the inhibiting factors of the communication role of Islamic Religious Education Teachers in fostering the morals of seventh grade students of SMP Negeri 36 Makassar. This research is a qualitative research at SMP Negeri 36 Makassar. Data was collected using several methods, namely observation, interviews, and documentation. The sources of data and the subject of this research are Islamic Religious Education Teachers and Class VII Students of SMP Negeri 36 Makassar in 2021. Data analysis was carried out in four stages, namely data collection and checking, data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1). The researcher sees that the communication of Islamic religious education teachers